The role of School Operational Assistance (BOS) fund management on the quality of educational programs and student achievement at public junior high schools in Mimika Baru District, Mimika Regency - Alamtiur Hutauruk; Mesak Iek; Risky Novan Ngutra (LPPM STIE KRAKATAU, 2025)
Purpose: This study aims to analyze the role of School Operational Assistance (BOS) fund management in enhancing the quality of educational programs and student achievement at public junior high schools in the Mimika Baru District, Mimika Regency. Research/methodology: The research employs a descriptive qualitative approach with a case study design conducted at SMP Negeri 2 Mimika and SMP Negeri 11 Mimika. Data were collected through in-depth interviews with school principals, treasurers, teachers, and school committee members, as well as through direct observation and document analysis. Data analysis followed the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. Results: The findings indicate that BOS fund management in both schools generally aligns with technical guidelines. The funds are effectively utilized to support infrastructure development, procure learning materials, finance extracurricular activities, and improve teacher competencies. As a result, the program contributes positively to both the quality of education and student academic performance. Conclusions: Effective management of BOS funds at SMP Negeri 2 and SMP Negeri 11 Mimika significantly contributes to improving educational quality and student achievement. The funds are utilized in accordance with technical guidelines to support infrastructure, learning materials, extracurricular activities, and teacher development. Stakeholder involvement also enhances transparency and accountability in fund utilization. Limitations: This study is limited to two schools and adopts a purely qualitative perspective, which may not represent broader regional conditions or allow for quantitative measurement of impact. Contribution: This research offers valuable insights for policymakers and school administrators regarding the effective utilization of BOS funds to improve education quality and student outcomes, particularly in remote and diverse educational settings.